Synchronization of two electrochemical oscillators in a closed bipolar cell - Tetteh, John A.; Kiss, István Z. (Frontiers in Complex Systems, 2024)
We investigate the dynamical behavior of the oscillatory electrodissolution of nickel and hydrogen reduction reaction in a closed electrochemical bipolar cell with two nickel wires. In the bipolar setup, two half U cells are separated by an epoxy plate with the two embedded nickel electrodes; the oxidation and reduction reactions take place at the two ends of the same wire. The electrode potential oscillations were found to be strongly synchronized with 1 mm diameter electrodes in an in-phase configuration. Because experiments in similar configurations with traditional (threeelectrode) cell showed no synchronization of the oscillatory anodic nickel electrodissolution, the introduction of the cathodic side of the bipolar electrodes induced the synchronization. The results were interpreted with a model that considered the kinetically coupled cathode-anode dynamics as well as interactions on the cathode and the anode side through migration current mediated potential drops in the electrolyte. The electrical coupling strength was calculated from solution resistance and charge transfer resistance measurements. The theory correctly interpreted that the bipolar cell with large (1 mm diameter) electrodes exhibits strong coupling with synchronization, and the bipolar cell with small (0.25 mm diameter) electrodes and the traditional configuration exhibit weak coupling and thus desynchronization. The experiments demonstrate the use of bipolar electrochemical cells for the investigation of collective behavior of electrochemical processes and the proposed approach holds promise for the design of bipolar multi-electrode arrays with engineered coupling to promote sensing and information processing using microchips.